Die Demontage der multilateralen Wirtschaftsordnung durch die Dritte Welle des Regionalismus - Dieter, Heribert (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2003)
Economic multilateralism is at risk. Both the World Trade Organisation and the International Monetary Fund are undermined by competing regimes at the regional level. Bilateralism in trade is particularly mushrooming and might flourish further after the brealcdown of talks in Cancun. Especially the USA are organising their trading relations outside the WTO. These new regimes both undermine multilateralism as well as strengthen the more powerful nations. Developing countries are once again at the receiving end.